2001
DOI: 10.1562/0031-8655(2001)073<0230:aofmpo>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fluoroquinolone-mediated Photosensitization of 2′-Deoxyguanosine, Calf Thymus and Cellular DNA: Determination of Type-I, Type-II and Triplet–Triplet Energy Transfer Mechanism Contribution¶

Abstract: Fluoroquinolone (FQ) antibacterials are known to exhibit photosensitization properties leading to the formation of oxidative damage to DNA. In addition, photoexcited lomefloxacin (Lome) was recently shown to induce the formation of cyclobutane pyrimidine dimers via triplet-triplet energy transfer. The present study is aimed at gaining further insights into the photosensitization mechanisms of several FQ including enoxacin (Enox), Lome, norfloxacin (Norflo) and ofloxacin (Oflo). This was achieved by monitoring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(102 citation statements)
references
References 44 publications
6
95
1
Order By: Relevance
“…These observations, which are in agreement with results obtained in CHO (28,30) and human skin cells (29), show that the mechanism of formation of CPDs upon UVA and UVB irradiation is different. The distribution of dimeric photoproducts suggests that a photosensitization reaction involving a triplet energy transfer mechanisms rather than a direct excitation process takes place upon exposure of skin to UVA, similarly to what is observed in the effects of some phototoxic drugs (49)(50)(51). Moreover, in contrast to a widely accepted hypothesis, we also found that, like in cultured cells (15,28,29), TϽϾT was produced in a larger amount than 8-oxodGuo in human skin exposed to UVA.…”
Section: Discussionsupporting
confidence: 67%
“…These observations, which are in agreement with results obtained in CHO (28,30) and human skin cells (29), show that the mechanism of formation of CPDs upon UVA and UVB irradiation is different. The distribution of dimeric photoproducts suggests that a photosensitization reaction involving a triplet energy transfer mechanisms rather than a direct excitation process takes place upon exposure of skin to UVA, similarly to what is observed in the effects of some phototoxic drugs (49)(50)(51). Moreover, in contrast to a widely accepted hypothesis, we also found that, like in cultured cells (15,28,29), TϽϾT was produced in a larger amount than 8-oxodGuo in human skin exposed to UVA.…”
Section: Discussionsupporting
confidence: 67%
“…Thus, T<>T formation is revealed by a specific repair enzyme: the T4 endonuclease V. Under the experimental conditions used and without enzymatic treatment, no single-strand breaks are photosensitized by NFX and ANFX. In agreement with previous observations based on HPLC-MS/MS analysis [17], NFX is able to photoinduce T<>T dimers as revealed by the detection of single-strand breaks after subsequent irradiation and enzymatic treatment (Fig. 4).…”
Section: Triplet-state Energy Of Thymine In Dna [27]supporting
confidence: 92%
“…Nevertheless, the ability of these drugs to induce DNA damage in the more complex environment characteristic of the whole cell, as well as the description of the modified bases and the possible molecular mechanisms involved in base alteration, have been less investigated. By contrast, fluoroquinolones have been shown to produce singleand double-strand breaks, as well as alkali-labile sites, by means of the comet assay [17,18].…”
Section: Photosensitization Of Cellular and Isolated Dna By 2-arylpromentioning
confidence: 99%
“…If true, thymine would be the main target because it has the lowest triplet state energy among all four DNA bases (48). Accordingly, sequence contexts of 5ЈTT, 5ЈTC, and 5ЈCT, respectively, are to be hit by UVA-derived triplet photosensitization reactions (49). In confirmation, most UVA1-induced CPDs along the p53 gene were formed at these sequence contexts, especially consequent to the highest irradiation dose.…”
Section: Discussionmentioning
confidence: 95%